2014
DOI: 10.1371/journal.pone.0097840
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Covering Behavior and Exposure to a Predatory Crab Charybdis japonica on Survival and HSP70 Expression of Juvenile Sea Urchins Strongylocentrotus intermedius

Abstract: Predation is a complex process among predator, prey and environment. Juvenile sea urchins are more susceptible to predators than adults, which affects community structure. Behavior is involved in anti-predator responses by changes in the expression of anti-predator responsive genes. Here, we investigated the effects of exposure to a predatory crab Charybdis japonica and covering behavior on survival and HSP70 expression of juvenile sea urchins Strongylocentrotus intermedius. C. japonica consumed large numbers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…We found that slow‐moving urchins were more likely to survive encounters with lobsters (Figure ), whereas covering behavior did not predict urchin survival on its own. This is consistent with findings suggesting that active prey are more likely to succumb to predation (Huey & Pianka, ; Perry, ), particularly with sedentary predators, and that urchin covering behavior does not regularly predict survival in a direct manner (Zhao et al, ). Urchin size also did not predict survival directly.…”
Section: Discussionsupporting
confidence: 89%
“…We found that slow‐moving urchins were more likely to survive encounters with lobsters (Figure ), whereas covering behavior did not predict urchin survival on its own. This is consistent with findings suggesting that active prey are more likely to succumb to predation (Huey & Pianka, ; Perry, ), particularly with sedentary predators, and that urchin covering behavior does not regularly predict survival in a direct manner (Zhao et al, ). Urchin size also did not predict survival directly.…”
Section: Discussionsupporting
confidence: 89%
“…We found that slow-moving urchins were more likely to survive encounters with lobsters (Figure 1), whereas covering behavior did not predict urchin survival on its own. This is consistent with findings suggesting that active prey are more likely to succumb to predation (Huey & Pianka, 1981; Perry, 2007), particularly with sedentary predators, and that urchin covering behavior does not regularly predict survival in a direct manner (Zhao et al, 2014). Urchin size also did not predict survival directly.…”
Section: Discussionsupporting
confidence: 89%
“…One study of Strongylocentrotus urchins found that covering can protect urchins in the lab setting from predation by crabs for short periods of time, up to 2 hours [1]. However, a more recent experimental study of these urchins found no correlation between amount of covering and presence of predators, suggesting that protection of this type is coincidental rather than a functional reason for heaping in this genera [37].…”
Section: Covering As Predator Protectionmentioning
confidence: 99%